KELUHAN MUSKULOSKELETAL PENGGUNA LAPTOP DAN SMARTPHONE PADA MAHASISWA STIKES INDONESIA PADANG SELAMA STUDI FROM HOME DIMASA PANDEMIC COVID-19 TAHUN 2021 - Gustina Indriati; Yeni Herlina (Ensiklopedia of Journal, 2022)
The implementation of educational policies in education as during emergency period of the Corona virus disease (Covid-19) includes home and online learning, which requires the use of supporting technology such as cellphones, computers, and tablets. The increasing number of hours spent on laptops or cellphones will have a variety of consequences, one of which is musculoskeletal issues. According to direct interviews, 3 out of 5 respondents had muscle issues after attending online lectures on a laptop or smartphone. The goal of this descriptive research was to describe the description of musculoskeletal symptoms caused by the usage of laptops or cellphones among students in the HKK StikesI study program's 2019 class. Time and place From April to November 2021, this study was conducted at STIKesI Padang with a population of 90 students from the 2019 HKK study program. A total sampling method was used to collect data using a Nordic Body Map questionnaire that was sent via an internet form. According to the results, 12.2 percent of respondents had moderate to severe musculoskeletal symptoms. Students with musculoskeletal difficulties should take a break after online learning and stretch their muscles to avoid uncomfortable learning positions and settings when studying online.Keyworlds: Learning online (SFH), Laptop, Musculoskeletal System (MsDs).